CORPORAL PRACTICES AND HEALTH PROMOTION - Fortin, Sylvie (Cena, 2016)
The paper analyzes the relations between corporal practices and health promotion, examining examples coming from the Dance Field. In a societal context in which body receives more and more attention, it is important that professionals in the field of art, physiotherapy, and physical education engage in critical reflexivity about values entangled in mainstream and alternative discourses.